2018
DOI: 10.1038/s41419-017-0162-9
|View full text |Cite
|
Sign up to set email alerts
|

FLI1 and PKC co-activation promote highly efficient differentiation of human embryonic stem cells into endothelial-like cells

Abstract: Rationale-endothelial cells (ECs) play important roles in various regeneration processes and can be used in a variety of therapeutic applications, such as cardiac regeneration, gene therapy, tissue-engineered vascular grafts and prevascularized tissue transplants. ECs can be acquired from pluripotent and adult stem cells. To acquire ECs from human embryonic stem cells (hESCs) in a fast, efficient and economic manner. We established a conditional overexpression system in hESCs based on 15 transcription factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Several groups have demonstrated the ability to differentiate ECs from human embryonic stem cells (hESC). 5–7 This protocol yields ECs that are relatively immature and express genes that are somewhat distinct from those of mature ECs from various vascular beds, 8 highlighting the importance of understanding the molecular mechanisms controlling both general and specialized EC differentiation, specification, and function. These derived ECs have been extensively proven to be functional both in vitro , by the ability to form capillary-like networks on Matrigel 7 and in vivo , by their ability to improve vascular density and perfusion in a murine model of hind limb ischaemia (HLI).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have demonstrated the ability to differentiate ECs from human embryonic stem cells (hESC). 5–7 This protocol yields ECs that are relatively immature and express genes that are somewhat distinct from those of mature ECs from various vascular beds, 8 highlighting the importance of understanding the molecular mechanisms controlling both general and specialized EC differentiation, specification, and function. These derived ECs have been extensively proven to be functional both in vitro , by the ability to form capillary-like networks on Matrigel 7 and in vivo , by their ability to improve vascular density and perfusion in a murine model of hind limb ischaemia (HLI).…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic stem cell (ESC) transplantation has greatly reduced the number of senile cells in bone marrow and improved the cell composition of the hematopoietic niche. [ 84 ] Therefore, reprogrammed ESCs are used to treat ischemic diseases because of their unique proliferation, survival characteristics, and hematopoietic derivation. Leung et al [ 85 ] developed a cell culture system and found that hematopoietic stem/progenitor cells (HSPCs) modified with ESC or iPSC genes produced myeloid and lymphoid hematopoietic cells with an enhanced colony-forming ability and hemoglobin expression to promote hematopoiesis in elderly individuals.…”
Section: New Approaches To Hematopoietic Niche Rejuvenationmentioning
confidence: 99%
“…To overcome these hurdles, human pluripotent stem cells (hPSCs) can be differentiated into endothelium. Attempts at efficient in vitro endothelial differentiation of hPSCs have been conducted for at least 10 years (Choi et al, 2009;Park et al, 2010;Vodyanik et al, 2010;Joo et al, 2011;Li et al, 2011;Tatsumi et al, 2011;Adams et al, 2013;Prasain et al, 2014;Sahara et al, 2014;Zhang et al, 2014;Bao et al, 2015;Patsch et al, 2015;Sriram et al, 2015;Kitajima et al, 2016;Ye et al, 2016;Harding et al, 2017;Olmer et al, 2018;Suknuntha et al, 2018;Zhao et al, 2018). This strategy has the potential to ensure a consistent and unlimited source of ECFCs for in vitro studies and regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Second, monolayer differentiation is a more feasible approach, with higher efficiency in a shorter time. There are multiple monolayer differentiation protocols that vary in both medium and cytokine supplement (Park et al, 2010;Joo et al, 2011;Tatsumi et al, 2011;Orlova et al, 2014;Prasain et al, 2014;Sahara et al, 2014;Bao et al, 2015;Patsch et al, 2015;Sriram et al, 2015;Kitajima et al, 2016;Harding et al, 2017;Zhao et al, 2018). Most monolayer protocols use single-cell seeding, small-clump seeding using ethylenediaminetetraacetic acid (EDTA), or larger-clump seeding using a needle.…”
Section: Introductionmentioning
confidence: 99%